2011
DOI: 10.1038/ejhg.2011.128
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Gypsy SHOX mutation (p.A170P) in Léri-Weill dyschondrosteosis and Langer mesomelic dysplasia

Abstract: We report the clinical and molecular characteristics of 12 Spanish families with multiple members affected with Lé ri-Weill dyschondrosteosis (LWD) or Langer mesomelic dysplasia (LMD), who present the SHOX (short stature homeobox gene) mutation p.A170P (c.508G4C) in heterozygosity or homozygosity, respectively. In all studied families, the A170P mutation co-segregated with the fully penetrant phenotype of mesomelic limb shortening and Madelung deformity. A shared haplotype around SHOX was observed by microsate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
6
2
Order By: Relevance
“…Thus, in my opinion, the conclusions in this paper are misleading since it is stated that the studied patient did not have radiological traits nor bone dysplasia in contrast to all previously reported A170P carriers,3 4 who were reported to have dysplastic features. Furthermore, in the discussion it is suggested that this ‘mutation shows a highly variable penetrance ’ .…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…Thus, in my opinion, the conclusions in this paper are misleading since it is stated that the studied patient did not have radiological traits nor bone dysplasia in contrast to all previously reported A170P carriers,3 4 who were reported to have dysplastic features. Furthermore, in the discussion it is suggested that this ‘mutation shows a highly variable penetrance ’ .…”
contrasting
confidence: 78%
“…Furthermore, in the discussion it is suggested that this ‘mutation shows a highly variable penetrance ’ . This statement, however, is not sufficiently supported by the data presented and is at odds with our own previous data,3 because as mentioned previously, the patient's x-ray does reveal radiological/dysplastic signs characteristic of LWD, and no anthropometrical examination was undertaken to explore mesomelic shortening and finally, most importantly, clinical and molecular analysis was not undertaken in other family members, which would have been indicated and very useful to properly assess penetrance.…”
contrasting
confidence: 75%
“…The population of European Gypsies is about 10 million; with more than 500,000 individuals in Spain, Slovakia, Hungary, Bulgaria and Romania . Many Mendelian disorders in European Gypsies are caused by private founder mutations and specifically in Spain and Portugal, about a dozen genetic diseases are highly prevalent in this ethnic group . In this study, we detected a new founder mutation in EIF2AK4 [c.3344C>T; (p.P1115L)] (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…Barca-Tierno et al (2011) have characterised 12 Spanish families affected with LWS or LMD, where 11 of them belong to the gypsy population. The authors state that A170P mutation is fully penetrant because it cosegregates with the phenotype of mesomelic limb shortening and Madelung deformity 8. Sabherwal et al presented a family with 17 members affected with LWD and LMD, all of them carrying the A170P mutation and all but one presenting with the Madelung deformity.…”
Section: Discussionmentioning
confidence: 99%